Expression of CD40 and CD40L on tumor cells: the role of their interaction and new approach to immunotherapy - Bereznaya, N.M.; Chekhun, V.F. (Experimental Oncology, 2007)
In the review the modern insights on the role of expression of CD40 and CD40L and the role of their interaction on tumor cells growth are analyzed. Information about the structure and biologic properties of these molecules and their interaction is presented. The question on the role of CD40/CD40L interaction is highlighted in two aspects – the possibility of tumor growth inhibition and its stimulation. According to the mentioned aspects, immunologic mechanisms providing tumor growth inhibition (the role of dendritic cells, macrophages, monocytes, cytotoxic T-lymphocytes, natural killer cells etc.), and also the possibility of apoptotic events are discussed. Possibility of tumor growth stimulation upon the influence of CD40/CD40L interaction that could occur in some cases is analyzed as well. The data of literature about new approaches to immunotherapy of cancer based on CD40/CD40L interactionare summarized. В обзоре представлены современные данные об экспрессии CD40 и CD40L опухолевыми клетками и значении взаимодействия
указанных молекул на этих клетках. Приведена информация о структуре и биологических свойствах этих молекул и их
взаимодействия. Вопрос о взаимодействии CD40/CD40L рассматривали в двух аспектах — возможность ингибиции роста
опухоли и стимуляции. В соответствии с этим изучают иммунологические механизмы, обеспечивающие торможение роста
опухоли (роль дендритных клеток, макрофагов, моноцитов, цитотоксических Т-лимфоцитов, естественных киллеров и др.), а
также возможность развития апоптоза. Рассматривают возможность стимуляции роста опухоли под влиянием CD40/CD40L
взаимодействия, что отмечают в отдельных случаях. Обобщены существующие данные доступной литературы о новых
подходах к иммунотерапии на основе анализа механизмов вышеуказанного взаимодействия.
Ключевые слова: CD40, CD40L, CD40/CD40L-взаимодействие, опухоль, иммунотерапия.